Solid waste management in North Klang area / Nurul Hidaya Jantan - Jantan, Nurul Hidaya (2007)
Everyday, human produce waste. Each of the area has a population should provided accurate disposal services. The cooperation from the entire person is important to ensure the good environment achieve. In Malaysia, every change of the total waste and types of waste depends on the growth of population. Solid waste management may be defined as the discipline associated with the control of generation, storage, collection, transfer and transport, processing, and disposal of solid wastes in a manner that is in accord with the best principles of public health, economics, engineering, conservation, aesthetics, and other environmental considerations, and that is also responsive to public attitudes. For this study, observation, questionnaires and interview has been conducted to identify the Solid Waste Management in North Klang. From this method, the entire weakness that occurs can be detected. The main point for this study is to identify the authorities operation, to discover the usual issue that occurs at the case study and to obtain the respondent feedback about this operation. The major issues on the solid waste management at the area are Klang is known as the black area because it is producing a lot of illegal dumps, the leachate compactor which there is leaking on the compactor plate and schedules are not properly followed by the contractor and also they did not reach their zone according to the time schedule. All the supervision is implementing by the authorities to ensure that the process is efficient and follow the appropriate schedule. Other than that, the public also play an important role to educate themselves on the importance of environmental cleansing. The effective of solid waste management is to help the government to produce an environmental friendly surrounding. The government should improve more on the technical expertise to obtain the efficiency in solid waste management in North Klang. The also government should suggest to all everybody to give cooperation to improve the quality of cleansing at this country.